Seminal papers in hand and wrist surgery. Issue 6 (December 2015) - Nash, William; Walker, Roland; Gidwani, Sam; Ajuied, Adil
Abstract: Evidence based medicine should underpin the practice of all orthopaedic surgeons. Hand and wrist conditions comprise one eighth of the FRCS viva, and questions on hand and wrist surgery also feature in the trauma viva and upper limb clinical cases. Consequently, detailed knowledge of hand and wrist pathologies and their management is critical for exam success. To meet the criteria of a classic paper within hand surgery it must refine or describe a technique, the techniques must survive the passage of time and it must change the course of treatment. We list 10 key articles which have been selected for their impact within the field.